Use of Guided Discovery Teaching Style in Learning Football Passing - Giptun Daksinanuaji; Aria Kusuma Yuda; Tedi Purbangkara (Edumaspul: Jurnal Pendidikan, 2024)
Physical and health education is one of the teaching and learning activities provided by teachers to students which aims to provide movement learning experiences as an effort to develop The potential possessed by students. Teaching style according to the term, namely (teaching style) is often replaced by the term teaching strategy (teaching strategy) whose meaning is considered the same, namely strategies to encourage student participation in carrying out the tasks given. This research was based on government efforts and policies that are in accordance with students' needs in learning and self-development, in terms of knowledge (cognitive), attitudes (affective) and movement skills (psychomotor). The aim to be achieved in this research is to reveal data regarding the use of the Guided Discovery Teaching Style in Learning Football Passing in Class VIII at SMP Negeri 2 Ciasem. This research uses a qualitative approach. The subjects of this research were the sources of information, namely 4 class VIII students studying at SMP Negeri 2 Ciasem and 1 teacher. Thus, the number of subjects for this research was 5 people. Keywords: Teaching style , Football passing , Guided discovery